Dielectric properties of nanostructure - Huang, Sai Feng. (2010)
With the miniaturization of semiconductor materials, the dielectric properties and optical properties of the material is changing when the device is been suppressed. Therefore, knowing the dielectric functions of semiconductor nanocrystals is critical important in the optoelectronic and microelectronic application. This report detailed the final project on the author researched of dielectric properties in nanostructure material such as nanocrystals. This report focused on two most well-known dielectric function models. They were Forouhi-Bloomer (FB) model and Lorenz Oscillator model. These two models were commonly used to calculate and estimate the dielectric functions when the device material is being suppress into nano scale. In the project, Germanium nanocrystals (nc-Ge) with different sizes deposited on the 3nm SiO2 layer have been synthesized with E-beam technique. The influence of nanocrystals size on the dielectric properties and optical properties, including dielectric functions and optical constants, of the nc-Ge has been investigated with spectroscopic ellipsometry. The dielectric properties are found to be well described by the two-term FB model and Lorentz oscillator model with Bruggeman effective medium approximation (EMA). A strong dependence of the dielectric functions and optical constants on the nc-Ge size is observed. The nc-Ge exhibits a significant reduction in the dielectric functions and optical constants compared with bulk crystalline Ge. A band gap expansion is also been observed when the nc-Ge size is reduced. The band gap expansion with the reduction of nc-Ge size could be related to the quantum trapping effect as a large band gap expansion observed is a result of the quantum trapping.